Targeted Genome Engineering to Control VEGF Expression in Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells: Potential Implications for the Treatment of Myocardial Infarction. (3rd January 2017) - Cho, Hyun-Min; Kim, Pyung-Hwan; Chang, Hyun-Kyung; Shen, Yi-ming; Bonsra, Kwaku; Kang, Byung-Jae; Yum, Soo-Young; Kim, Joo-Hyun; Lee, So-Yeong; Choi, Min-cheol; Kim, Hyongbum (Henry); Jang, Goo; et al.
Abstract: Human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) exhibit potency for the regeneration of infarcted hearts. Vascular endothelial growth factor (VEGF) is capable of inducing angiogenesis and can boost stem cell-based therapeutic effects. However, high levels of VEGF can cause abnormal blood vessel growth and hemangiomas. Thus, a controllable system to induce therapeutic levels of VEGF is required for cell therapy. We generated an inducible VEGF-secreting stem cell (VEGF/hUCB-MSC) that controls the expression of VEGF and tested the therapeutic efficacy in rat myocardial infarction (MI) model to apply functional stem cells to MI. To introduce the inducible VEGF gene cassette into a safe harbor site of the hUCB-MSC chromosome, the transcription activator-like effector nucleases system was used. After confirming the integration of the cassette into the locus, VEGF secretion in physiological concentration from VEGF/hUCB-MSCs after doxycycline (Dox) induction was proved in conditioned media. VEGF secretion was detected in mice implanted with VEGF/hUCB-MSCs grown via a cell sheet system. Vessel formation was induced in mice transplanted with Matrigel containing VEGF/hUCB-MSCs treated with Dox. Moreover, seeding of the VEGF/hUCB-MSCs onto the cardiac patch significantly improved the left ventricle ejection fraction and fractional shortening in a rat MI model upon VEGF induction. Induced VEGF/hUCB-MSC patches significantly decreased the MI size and fibrosis and increased muscle thickness, suggesting improved survival of cardiomyocytes and protection from MI damage. These results suggest that our inducible VEGF-secreting stem cell system is an effective therapeutic approach for the treatment of MI.